Anatomopathological findings and identification of Cryptococcus gattii in a captive African pygmy hedgehog (Atelerix albiventris) - Zanoti, Isabela Coelho; Machado, Eduardo Ferreira; Figueiredo, Ketlyn Bolsachini; Carvalho, Ana Carolina Souza Ramos de; Bezzon, Camila de Paula e Silva; Andreato, Julia; Melo, Mayara de; Guerra, Juliana Mariotti (Brazilian Journal of Veterinary Pathology, 2023)
The African pygmy hedgehog (Atelerix albiventris) is becoming increasingly common in zoological collection and as pets, increasing the risk of disease transmission. Here, we describe a case of cryptococcosis caused by Cryptococcus gattii in a captive African pygmy hedgehog and the other anatomopathological findings. The macroscopic analysis of the lung found white-yellowish masses of gelatinous consistency. The microscopic analysis of the lung revealed severe pulmonary involvement resulting from granulomatous pneumonia caused by C. gattii yeasts, identified through polymerase chain reaction and sequencing. Other histopathological findings included hepatic steatosis, biliary hyperplasia, and renal lesions with deposition of hyaline cylinders in the lumen of tubular epithelial cells, glomerulopathy, and tubular necrosis. Our findings demonstrate the importance of anatomopathological studies in diagnosing relevant diseases in the context of one health. We emphasize that adequate environmental management is essential to avoid the emergence of certain diseases in captivity.